RETORNO AO FEUDALISMO? ALGUNS ASPECTOS SOCIAIS, ECONÔMICOS, POLÍTICOS E JURÍDICOS DO MEDIEVO E DA ATUALIDADE: APROXIMAÇÕES E DISTINÇÕES: (Reflection and Critique Law Magazine, 2022)
The study, elaborated from bibliographic research and under the inductive method, addresses the issue of the return to feudalism in social, economic, political and legal spheres, called “neofeudalism”, “refeudalism”, “neomedievalism” or “new Middle Ages”. Initially the positions of the scholars who raise the problem are mentioned, then the general characteristics of these areas are described, first in the Middle Ages and then today, which, finally, are compared, to conclude that there is no return to that period.